(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article aims to analyze the legislative changes brought by the Labor Reform, specifically about the attorney’s fees for defeat, which was the object of the Direct Unconstitutionality Action 5.766 proposed at the Supreme Court in view of the possible affront to the constitutional precepts of free access to justice, as well as the benefits obtained by those who get the free administration of justice. The constitutional affront would be evidenced to the extent that the unsuccessful claimant would be required to pay the defeat fees or in his unjustified absence from the labor hearing. Finally, this article is not dedicated to the exhaustion of the proposed theme, but aims to question whether the imposition of the payment of fees actually violates constitutional provisions and whether this factor limits access to justice.